History and management of congenital aortic stenosis and coarctation of the aorta in a 38-year-old patient - Wojarska, Izabela; Bednarek, Jadwiga; Nowak, Ewelina; Polewczyk, Anna (Medical Studies/Studia Medyczne, 2019)
We present the case of a 38-year-old woman with congenital aortic stenosis as well as coarctation of the aorta that was unrecognised in her childhood. The patient was treated by balloon valvuloplasty. Ten years after the procedure, clinical deterioration was observed with subsequent progression of valvular gradient, aortic regurgitation, and diagnosis of coarctation. At the age of 38 years, a routine echocardiographic test showed massive calcifications of aortic leaflets with a transvalvular gradient 77/41 mm Hg, and third-degree insufficiency with widening of the ascending aorta (42 mm) and normal left ventricle systolic function. Additionally, for the first time the test showed coarctation of the aorta – narrowing in the isthmus below the arch down to 15 mm, with a maximum flow gradient ca. 60 mm Hg. The management of the complex heart defects is currently being considered.